(untitled) (Conferencea, 2024)
This article demonstrates the importance of ultrasound examination in diagnosing lower abdominal pain during pregnancy and ensuring fetal safety. It outlines the differences between physiological and pathological pain, the causes of pain, and diagnostic methods using ultrasound. The importance of timely diagnosis and fetal safety assurance through ultrasound examination is emphasized.